Socialist political economy with Chinese characteristics in a new era. Issue 2 (22nd December 2020) - Hong, Yinxing
Abstract : Purpose: The socialist political economy with Chinese characteristics reflects the characteristics of ushering into a new era, and the research object thereof shifts to productive forces. Emancipating and developing productive forces and achieving common prosperity become the main theme. Wealth supersedes value as the fundamental category of economic analysis. Design/methodology/approach: The theoretical system of socialist political economy with Chinese characteristics cannot proceed from transcendental theories but is problem-oriented. Leading problems involve development stages and research-level problems. Findings: The economic operation analysis is subject to the goal of optimal allocation of resources with micro-level analysis focused on efficiency and macro-level analysis focused on economic growth and macroeconomic stability also known as economic security. The economic development analysis explores the laws of development and related development concepts in compliance with laws of productive forces. The new development concepts i.e. the innovative coordinated green open and shared development drive the innovation of development theory in political economy. Originality/value: Accordingly, the political economy cannot study the system only, but also needs to study the problems of economic operation and economic development. Therefore, the theoretical system of the political economy tends to encompass three major parts, namely economic system, economic operation and economic development (including foreign economy). The basic economic system analysis needs to understand the relationship between public ownership and non-public ownership, between distribution according to work and factor payments, and between socialism and market economy from the perspective of coexistence theory, thus transforming institutional advantage into governance advantage.